O índice de sustentabilidade empresarial e a percepção do investidor: um estudo das empresas entrantes no índice nos anos de 2011 a 2013 - Silva, Moisés Ávila da (2013)
According to ISE (Corporate Sustainability Index), applications denominated socially responsible investment considers that sustainable companies create long term value to shareholders because they are more prepared to face environmental, social and economic risks. This demand has been strengthening over time and today is extensively attended by many financial instruments in the local and international market. In this context, this study analyzed the inclusion of companies, from 2011 to 2013, to socially responsible company s portfolio (Corporate Sustainability Index), evaluated a set of indicators of stock prices before and after the inclusion in the ISE, compared stock markets performance before and after the announcement of the inclusion. The objective, through the events study, was to evaluate if the investor had value aggregated to its equity by decision of the company s managers to enter the ISE. Inside this context, it also evaluated if the market announcement that they are socially correct companies was able to imply this perception and if stockholders had above average return because of this event. The results observed in this paper (in average) show indication that the market positively evaluates the sustainability efforts and is willing to repay for that. However, this reality doesn t hold for long. For 2013, a new fact that hadn t occurred before can be observed: the indication of a turnaround in the markets perception regarding sustainability efforts by companies. This year, the abnormal returns (WEG companies) continued after the announcement of entering the index. This fact can indicate that the announcement could have been able to increase the stockholder wealth